Contribution to the knowledge of the genus Neuraphes Thomson (Coleoptera: Staphylinidae: Scydmaeninae) in China - Zhou, De-Yao; Li, Li-Zhen (Zootaxa, 2016)
Two new species of the ant-like stone beetle genus Neuraphes Thomson, 1859 (Scydmaeninae: Glandulariini) from Sichuan Province are described: N. (Pararaphes) shu sp. n. and N. (Pararaphes) xilingensis sp. n., their aedeagi are illustrated. A single female of the nominotypical subgenus from Heilongjiang Province is also recorded.